The requirement of the exhaustion of internal remedies in the administration of social assistance in South Africa - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.